Analysis of renal calcular disease among children: our tertiary care experience - Kanth, Anzeen Nazir; Khan, Suhail Masood; Khan, Azhar Ajaz; Khan, Aymen Masood; Kanth, Irtifa Nazir (International Journal of Contemporary Pediatrics, 2021)
Background: Renal calcular disease is a common disorder that affects patients of all age groups. Paediatric age group is no exception and due to lack of timely intervention it can prove disastrous in the years to come. This study is aimed to assess and evaluate the clinical and metabolic profile of paediatric patients presenting with renal calculi. The research was conducted in a cross-sectional manner. Methods: The research enrolled a total of 254 urolithiasis patients aged 14 or less who presented to G. B. Panth hospital Srinagar. Structured history and relevant investigations were collected from all the patients. The physical exam, blood chemistry, and metabolite excretion in the urine (urinary calcium, citrate, magnesium, and oxalate) were all recorded. Results: There were 65 percent males and 35 percent females (2:1) among the 254 patients, with an average age of 8.15±5.04 years at presentation. In 54% of the patients, hypertension was discovered. Urea and creatinine levels were respectively 73.01, 59 mg/dl and 4.45, 4.01 mg/dl. The amount of PTH in the blood was 51.2931 pg/l. The calcium and phosphorus levels in the blood were 8.44±1.14 and 5.0234±0.895, respectively. Metabolic irregularities were discovered in 95 percent of the patients. Hypercalciuria was the most prevalent (54%), followed by hyperoxaluria (28%). In 21% of the patients, hypocitraturia was observed. In 7.8% of children, distal renal tubular acidosis was discovered. Just 4.7% of the children had a magnesium deficiency in their urine. Conclusions: The majority of children with stone disease have a metabolic risk factor, with hypercalciuria being the most frequent in our environment.